Appointment of Brother A. Manuel, FSC as De La Salle College president - De La Salle College (Animo Repository, 1950)
Upon the death of Brother Lucian Athanasius, FSC, on May 27, 1950, Brother A. Manuel, FSC, received his appointment as De La Salle College President. Brother Manuel arrived from the United States on September 16, 1949. When Brother L William died in October, 1949, Bro. Manuel became the Sub-Director of the Brothers' Community.